The features of the concept of mass customization - Davidavičius, Sigitas; Skačkauskienė, Ilona (Business: Theory and Practice, 2015)
In order to achieve competitive advantage organizations are forced to analyse and discuss application possibilities of customized solutions. Unfortunately, the application of such solutions is associated with increases in costs, raising the time of delivery and decreasing the level of quality compared to mass-produced products. Circa 1990 the concept of mass customization was proposed which solved mentioned problems and which, compared to the mass production, has properties necessary for more efficient adaptation to changing market conditions without making concessions in price, quality and delivery time. This paper analyses the concept of mass customization aiming to define research area in order to adapt the concept for service organizations. The analysis of mass customization definitions presented in the literature was processed and summary presented, this enabled to identify the main dimensions which are characterizing mass individualization. The main types of mass customization were presented and analysed in this article as well. Comparative literature analysis, abstraction and synthesis methods were applied during the research. The results of analysis enabled to formulate guidelines of further research.Masinio indvidualizavimo koncepto ypatumaiSantraukaSiekdamos  konkurencinio  pranašumo  organizacijos  priverstos  analizuoti,  svarstyti  individualizuotų  sprendimų  taikymo galimybes. Deja, tokių sprendimų taikymas siejamas su didėjančiomis išlaidomis, ilgėjančiu teikimo laiku ir mažėjančiu kokybės lygiu lyginant su masiniu būdu gaminamais produktais. Apie 1990 m. pasiūlytas tokių problemų sprendinys – masinis individualizavimas, kuris, lyginant su masine gamyba, turi savybių, būtinų efektyvesniam prisitaikymui prie kintančių rinkos sąlygų,  nedarant  nuolaidų  produktų  kainai,  kokybei  ir  teikimo  laikui.  Straipsnyje  analizuojama  masinio  individualizavimo  koncepcija siekiant apibrėžti tyrimų erdvę, adaptuojant ją paslaugas teikiančioms organizacijoms. Išanalizavus ir apibendrinus literatūroje pateikiamas masinio individualizavimo apibrėžtis, identifikuotos pagrindinės masinį individualizavimą nusakančios dimensijos, pateikti ir išanalizuoti masinio individualizavimo tipai. Remiantis atlikta analize suformuluotos tolimesnių tyrimų gairės. Straipsnyje taikyti lyginamosios analizės, abstrakcijos ir sintezės metodai.Reikšminiai žodžiai: masinis individualizavimas, koncepcija, paslaugos, viešosios paslaugos.